Historic Watermills of North America A Visual Preservation. - Boyd, Ken, 1952- (University of Alabama Press, 2020)
"This volume presents a gallery of stunningly beautiful images of 112 watermills still standing on the North American landscape. In somewhat idealized and romantic full-color photographs, Ken Boyd hearkens back to a nostalgic time after European settlement when these structures were the heart of their communities as they did the work of everyday living-grinding corn and wheat into meal and flour, or planing trees into timber for construction, or looming cloth from wool or cotton thread, or squeezing apples to make cider. In short, these mills turned the energy of flowing water into mechanical muscle for the benefit of their operators and customers. At one time vital to their surrounding regions, most of these surviving mills are in rural areas that have been passed over by the destructive hand of development. Some have been converted into homes or museums or are part of local tourist attractions, some have been abandoned but yet show the significance of their heydays, and others are still in use, doing the same work they have always done. Situated primarily on small waterways and feeder streams rather than on major rivers where catastrophic floods could have destroyed them, watermills often reflect the individuality of their builders and local construction materials, as well as the constraints or advantages of their physical locations. They are sometimes associated with low dams, upper and lower mill ponds, and/or covered bridges. In seeking out these extant structures to record them on film, Boyd has travelled far and wide over the continent. The images chosen for the book represent many types of watermills in almost every state of the Union and several Canadian provinces. Each photograph is accompanied by a caption stating the name of the mill, its location, date of construction, and brief comments highlighting its remarkability. Introductory text offers dimension and background to the images. This large-format trade book should appeal to local historians, museums, bookstores, and libraries where mills are located; to photographers and artists; to mill enthusiasts the world over; and to the general reading public"--